UPDATING EDUCATIONAL CONTENT IN THE ERA OF GLOBALIZATION (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2025)
This article examines the issues of updating the content of education in the era of globalization. In today's world, the rapid development of science and technology necessitates the implementation of modern approaches in the education system. From this perspective, the article explores innovative pedagogical technologies, the significance of the digital learning environment, and the need to improve curricula in line with international standards. Additionally, it analyzes interactive teaching methods and approaches aimed at fostering creative thinking in the learning process. The research findings provide practical recommendations for modernizing educational content.